2009
DOI: 10.1007/s10668-009-9220-5
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and awareness of eco-sanitation in central Nepal: a questionnaire survey

Abstract: This study is based on a visual inspection and a questionnaire survey about sanitation in central Nepal. A total of 201 people from different groups were asked about their knowledge about eco-toilets, the fertilizer value of human urine and wood ash. Farmers were the least educated and least aware of most of the topics asked. Although the majority of educated people were aware about urine fertilizer, 68% of them were not interested in its use in their home, and 39% of them said that it might be not accepted. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…It was further observed that about (Mubarak, 2013;Ashebir et al, 2013), cleanliness of toilet facility (Tumwebaze et al, 2014), poverty, shortage of water supply, lack of housing and illiteracy (Balamurugan et al, 2013). In another study by Pradhan and Heinonen (2010) in Central Nepal, it was observed that hygienic practices are influenced by the level of education largely because of lack of awareness among different socioeconomic strata. A research by Ashebir et al (2013) suggest that it is not enough to provide people with sanitation hardware because they may not be used by the intended users, which correspond to the observation made in this study.…”
Section: Status Of Latrine Usementioning
confidence: 98%
“…It was further observed that about (Mubarak, 2013;Ashebir et al, 2013), cleanliness of toilet facility (Tumwebaze et al, 2014), poverty, shortage of water supply, lack of housing and illiteracy (Balamurugan et al, 2013). In another study by Pradhan and Heinonen (2010) in Central Nepal, it was observed that hygienic practices are influenced by the level of education largely because of lack of awareness among different socioeconomic strata. A research by Ashebir et al (2013) suggest that it is not enough to provide people with sanitation hardware because they may not be used by the intended users, which correspond to the observation made in this study.…”
Section: Status Of Latrine Usementioning
confidence: 98%
“…This claim is supported by the opinion presented by Pradhan and Heinonen-Tanski (2010) who reported that active discussion is more effective than only giving information about eco-toilet.…”
Section: Awareness and Acceptancementioning
confidence: 73%
“…The spectre of the hunger and shortage of food might have been the reason that poor rural Nepalese, often illiterate women, were receptive to the idea of using human urine to increase food plant yields. On the contrary the richer people were more likely to say that this does not belong to their culture [33].…”
Section: In Tropical Developing Countries Urine Would Be An Especialmentioning
confidence: 90%